2014
DOI: 10.25105/me.v22i3.3194
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kebijakan Makroekonomi Dan Kualitas Kelembagaan Terhadap Foreign Di¬rect Investment Di Asean 6

Abstract: <p><em>Foreign Direct Investment (FDI) flow is one of the most important factor in the era of glob­alization. FDI in domestic receives extraordinay attention due to FDI could expand the production and enchance the performance of financial market. In the atmospher of globali­zation, FDI is one of the tools for developing countries to increase their economy. This re­search aims to analyze the factors the influence FDI capital inflow into ASEAN countries, i.e. Indonesia, Singapore, Malaysia, Thailand,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…In an equilibrium condition, the amount of saving must be equal to investment, and this shows that the level of investment actually depends also on the level of income, in the sense that the greater the income, the greater the level of investment, or vice versa. The results of this study are consistent with previous research by Sarwedi (2002: 32), Surianti (2011), Febrina (2014), and Letarisky (2014: 1) that the GDP variable or gross domestic product has a positive and significant effect on foreign direct investment. However, the results of other researchers Sambodo (2003) state that the GDP variable has a positive and significant effect when a crisis occurs.…”
Section: Variable Gross Domestic Product (Gdp)supporting
confidence: 92%
“…In an equilibrium condition, the amount of saving must be equal to investment, and this shows that the level of investment actually depends also on the level of income, in the sense that the greater the income, the greater the level of investment, or vice versa. The results of this study are consistent with previous research by Sarwedi (2002: 32), Surianti (2011), Febrina (2014), and Letarisky (2014: 1) that the GDP variable or gross domestic product has a positive and significant effect on foreign direct investment. However, the results of other researchers Sambodo (2003) state that the GDP variable has a positive and significant effect when a crisis occurs.…”
Section: Variable Gross Domestic Product (Gdp)supporting
confidence: 92%
“…The result shows that a stable institutional framework will drive economic growth, while weak institutional activity causes stagnant economic growth (Jain et al, 2017). Buchanan et al (2012), in their study of institutional quality with FDI-flow, conclude that institutional quality strongly influences FDIflow; thus, the institutional quality significantly provides positive impact on FDI (Febrina & Sumiyarni, 2014). The study is statistically not much different from Globerman and Shapiro (2002) who examine institutions with their foreign investment.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Empirical research shows that institutional quality is an independent variable, one of which is research (Febrina, P., 2014) , his research concluded that institutional quality has a positive effect on Foreign Direct Investment (FDI). (Huang, 2010) found a positive impact of increasing the country's political stability (an indicator of institutional quality) on financial development.…”
Section: Introductionmentioning
confidence: 99%